The Influence of Brand Image, Product Quality, and Price on Purchasing Decisions of Y.O.U Sunscreen - Apriyanti, Apriyanti; Rahmi, Palupi Permata (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to analyze the influence of brand image, product quality, and price on purchasing decisions of Y.O.U sunscreen. The research method used is a quantitative approach with probability sampling techniques through simple random sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that brand image and product quality have a positive and significant influence on purchasing decisions, while price has a negative influence on purchasing decisions.